2020
DOI: 10.21203/rs.3.rs-18330/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linagliptin, when compared to placebo, improves CD34+ve Endothelial Progenitor Cells in Type 2 diabetes subjects with chronic kidney disease taking metformin and/or insulin, a randomized controlled trial.

Abstract: Introduction: Endothelial Progenitor cells (EPCs) has been shown to be dysfunctional in both Type 2 Diabetes and Chronic Kidney Disease (CKD) leading to poor regeneration of endothelium and renal perfusion. EPCs have been shown to be a robust cardiovascular disease (CVD) risk indicator. Cellular mechanisms of DPP4 inhibitors such as Linagliptin (LG) on CVD risk, in patients with Type 2 Diabetes with established CKD has notbeen established. Hypothesis : Linagliptin, a DPP4 inhibitor when added to insulin, metfo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Our recent study using Linagliptin showed protection from renal injury with patients taking Linagliptin for a duration of 12 weeks [44]. However the difference between Linagliptin and placebo was not picked up by urine albumin: creatine ratio but was noted on assessing urinary exosome podocyte markers.…”
Section: Urine Podocyte Function Marker Quantification Of Exosomal Prmentioning
confidence: 93%
See 1 more Smart Citation
“…Our recent study using Linagliptin showed protection from renal injury with patients taking Linagliptin for a duration of 12 weeks [44]. However the difference between Linagliptin and placebo was not picked up by urine albumin: creatine ratio but was noted on assessing urinary exosome podocyte markers.…”
Section: Urine Podocyte Function Marker Quantification Of Exosomal Prmentioning
confidence: 93%
“…Arterial stiffness assays also help define endothelial function independent of serum assays but corelates well to standard biochemical assays that are used to define endothelial function [41,42]. In our previous studies using two di-peptylpeptidase inhibitors (DPP4i) such as saxagliptin and linagliptin in type 2 diabetes mellitus (T2DM) patients [43,44] we have demonstrated that CD34+ve cells are responsive to a change in therapy or intervention within 2-4 weeks using CD34+ as a biomarker and CD34+ cell based assays can be used as a reliable non serum based cellular bio-marker. The same is true for of a prediabetes population with an aerobic exercise intervention, where changes in gene expression are quite fast [29].…”
mentioning
confidence: 99%